Keragaman Struktur Tegakan Hutan Alam Sekunder (The Variability of Stand Structure of Logged-over Natural Forest) - Muhdin; Istomo; Endang Suhendang; Djoko Wahjono; Herry Purnomo; Bintang C.H. Simangunsong (Institut Pertanian Bogor (IPB University), 2008)
Differences in logging intensity, forestfires and forest encroachment have caused the variability of natural forest conditions, including its horizontal and vertical stand structures. Information on stand structure variability and dynamic of secondary forests is essential for projecting the future stand structure, which can be used to develop forest management plan. This study, which used 109 permanent sample plots data established on low and dry-land logged over natural forests in Kalimantan, showed that there was an obvious variability of the stand conditions after logging in terms of the trees number per hectare and horizontal stand structures.